Can gamification help to improve education? Findings from a longitudinal study. (September 2020) - Putz, Lisa-Maria; Hofbauer, Florian; Treiblmaier, Horst
Abstract: A goal of any educational measure is to improve students' capability to retain teaching content. In this paper, we investigate the potential of gamification to foster knowledge retention using an action research approach. We present the results from a longitudinal study including 617 secondary and tertiary education students conducted over a period of two years. Various workshop designs that incorporated numerous gamification elements were compared with non-gamified workshop designs, tested and refined over time. The improved workshop designs led to increased levels of knowledge retention that exceeded the benchmark values from educational literature. We found that gamification exerts a positive impact on knowledge retention. We tested for the moderating effects of gender and age and found no effect of the former and inconsistent results for the latter. The steady increase in students' learning performance resulting from constant refinement of the workshops demonstrates the usefulness of incorporating gamification principles into educational activities. Highlights: Gamification has a positive effect on students' knowledge retention. The positive effect of gamification is independent of age and gender. Game elements can be used to tailor workshops to students' needs.